2019
DOI: 10.1080/1177083x.2019.1680396
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of palliative care educational intervention in long-term care: a qualitative multi-perspective investigation

Abstract: In industrialised countries, a large number of older adults with increasingly complex end of life care needs will die while in longterm care. It is essential that processes be in place to facilitate quality end of life care in these settings. In collaboration with two local hospices over the course of one year, we developed a new model of palliative care within long-term care-Supportive Hospice Aged Residential Exchange (SHARE). SHARE fostered knowledge exchange between hospice nurses and long-term care staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…There are several studies making a strong case for the significant impact that formal palliative care training can have on clinical staff care delivery when palliative care is integrated into their clinical patient care work 12–14 and a variety of educational approaches have been referred to in the literature, including on-site sessions and distance learning, 15 study half days, 16 simulation study days 17 18 and ongoing training programmes. 19 20 …”
Section: Designmentioning
confidence: 99%
“…There are several studies making a strong case for the significant impact that formal palliative care training can have on clinical staff care delivery when palliative care is integrated into their clinical patient care work 12–14 and a variety of educational approaches have been referred to in the literature, including on-site sessions and distance learning, 15 study half days, 16 simulation study days 17 18 and ongoing training programmes. 19 20 …”
Section: Designmentioning
confidence: 99%
“…The SHARE intervention was implemented over a year in 20 urban RAC facilities across two district health boards (DHBs) in one urban centre. This paper forms part of a larger mixed-method evaluation of SHARE which included quantitative assessments of staff palliative care delivery confidence, a records review of residents identified as benefitting from a palliative approach to care, as well as qualitative interviews with staff, general practitioners (GP's), facility managers and bereaved families [23].…”
Section: Introductionmentioning
confidence: 99%
“…The SHARE intervention was implemented over a year in 20 urban RAC facilities across two district health boards (DHBs) in Auckland. This paper forms part of a larger mixed-method evaluation of SHARE which included quantitative assessments of staff palliative care delivery con dence, a records review of residents identi ed as bene tting from a palliative approach to care, as well as qualitative interviews with staff, general practitioners (GP's), facility managers and bereaved families (23).…”
Section: Introductionmentioning
confidence: 99%